A gleam of hope for the critically endangered Isoëtes malinverniana: Use of small‐scale translocations to guide conservation planning. Issue 2 (17th November 2017) - Abeli, Thomas; Cauzzi, Paolo; Rossi, Graziano; Pistoja, Fausto; Mucciarelli, Marco
Abstract: Results of the first documented reintroduction of the endangered endemic quillwort Isoëtes malinverniana are presented 1 year after transplanting. This represents the most complete report of a quillwort translocation globally. A new population of I. malinverniana was established in a protected area in Lombardy (northern Italy) after several years of investigation of the ecology, biology and genetics of this species. The selected site was restored before the trial release in March 2016 of 20 individuals of the target species. Although modelling for the selection of suitable release sites for the target species indicated that the selected site was not suitable for the species, I. malinverniana exhibited a survival of 60% 1 year after reintroduction. This trial indicates that with very rare species, experimental trialling of a few individuals can test the feasibility of translocation at a larger scale. Although the model was constructed using a wide variety of ecological and phenological parameters, it was unreliable because of intrinsically low statistical power, which is a limitation of modelling associated with very rare species. Although mature spores were dispersed in autumn 2016, sporelings have not yet been observed. Ultimately, reintroduction of I. malinverniana will rely on the evidence of self‐recruitment; however, this translocation effort promoted understanding of ecological tolerance and facilitated focused conservation management. For instance, a protocol for in vitro reproduction of the species was successfully developed, resulting in long‐term survival of ex situ collections that exist in two botanical gardens in Pavia and Turin. Considering that many isoëtid species are threatened worldwide, the techniques applied here may have broad applicability to other endangered species.